Mitochondrial dysfunction-related metabolite methylmalonic acid is associated with decreased cognitive performance - Yige Liu; Jiaxin Wang; Pengyan Wu; Fan Tang; Wanlu Guo; Ruishan Li; Xinran Wang; Yiying Zhang; Shaohong Fang (PLoS ONE, 2025)
Purpose Methylmalonic acid (MMA), a mitochondrial metabolite derived from propionate metabolism, has been implicated in fatal neurodegeneration in children with congenital methylmalonic acidemia. However, its clinical relevance in chronic cognitive decline remains poorly understood. This study aims to investigate the association between MMA levels, its metabolic coenzyme vitamin B12, and cognitive impairment in an elderly population. Patients and methods The cohort comprised 2,762 participants aged 60 and older, who underwent assessments using the Digit Symbol Substitution Test (DSST), Animal Fluency test (AFT), Consortium to Establish a Registry for Alzheimer’s disease (CERAD) Immediate Recall (CERAD-IR), CERAD Delayed Recall (CERAD-DR), with low cognitive performance defined as the bottom quartile. Generalized linear regression models were applied to explore potential associations. Additionally, differentially expressed genes (DEGs) in MMA-related propionate metabolic process were identified from the RNA expression profiles in frontal cortex from 56 Alzheimer’s disease and 44 non-dementia controls. Results Among the 2,762 participants, with a mean age of 69.2 years and 53.8% female, elevated MMA levels were significantly associated with an increased likelihood of low cognitive performance across multiple tests: DSST (OR = 1.95; 95% CI: 1.41–2.73), AFT (OR = 1.51; 95% CI: 1.01–2.25), CERAD-IR (OR = 1.58; 95% CI: 1.19–2.09), and CERAD-DR (OR = 1.56; 95% CI: 1.12–2.18). High serum vitamin B12 levels were associated with an increased likelihood of impaired CERAD-IR scores, although dietary B12 supplementation did not correlate with cognitive performance. Stratified analyses revealed a stronger relationship between MMA and cognitive decline in males, individuals over 75 years, and those with elevated serum and dietary vitamin B12 levels. DEG analysis identified genes related to MMA synthesis and mitochondrial function in cognitively impaired individuals, with significant enrichment in mitochondrial propionate metabolism pathways. Conclusion The findings indicate that elevated MMA levels are linked to cognitive decline in older adults, potentially through mitochondrial dysfunction. These results underscore the clinical importance of MMA in the context of chronic cognitive impairment.